2018
DOI: 10.1016/j.jad.2017.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Robust symptom networks in recurrent major depression across different levels of genetic and environmental risk

Abstract: Similar depressive symptom networks for MD patients with a higher or lower genetic or environmental risk suggest that differences in these etiological influences may produce similar symptom networks downstream for severely depressed women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
70
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 59 publications
(89 reference statements)
4
70
1
4
Order By: Relevance
“…Second, the bootnet package in R (R Core Team, 2013) uses three bootstrapping routines to examine the stability of edge weight and node centrality estimates within networks. (1) A non-parametric bootstrap draws many (e.g., 1000; Fried et al, 2018) different subsamples with replacement from the observed data. The network edges estimated in these subsamples are pooled to generate a sampling distribution for each edge.…”
Section: Current Psychopathology Network Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, the bootnet package in R (R Core Team, 2013) uses three bootstrapping routines to examine the stability of edge weight and node centrality estimates within networks. (1) A non-parametric bootstrap draws many (e.g., 1000; Fried et al, 2018) different subsamples with replacement from the observed data. The network edges estimated in these subsamples are pooled to generate a sampling distribution for each edge.…”
Section: Current Psychopathology Network Methodsmentioning
confidence: 99%
“…Finally, the NCT package (van Borkulo et al, under review) uses permutation testing to quantify differences between pairs of networks with, ideally, similar sample sizes. This test works by pooling the data from the two networks that are being compared, and then repeatedly randomly re-assigning the data into two groups to estimate many (e.g., 5000 ;Fried et al, 2018) new pairs of networks. This process results in a reference distribution of differences between the two networks, representing the null hypothesis that the networks are drawn from the same population.…”
Section: Current Psychopathology Network Methodsmentioning
confidence: 99%
See 3 more Smart Citations